Efek Kecerdasan Emosional, Perilaku Belajar dan Penggunaan Media Sosial terhadap Prestasi Belajar Mahasiswa - Asri, Asri (Al-Buhuts, 2024)
The purpose of this study is to identify and analyze the influence of emotional intelligence, learning behavior, and social media use on student learning achievement. This study uses a quantitative approach with a survey design. The population in this study is 177 S1 students of the Nobel Institute of Technology and Business Indonesia In determining the number of research samples to be used as respondents in this study, it was determined using the Slovin formula, a total of 64 research samples were obtained with the sampling technique used was accidental sampling. The data analysis technique uses multiple linear regression analysis. The results of the study found that emotional intelligence had a positive and significant effect on student learning achievement, learning behavior had a positive and significant effect on student learning achievement and the use of social media had a positive and significant effect on student learning achievement.